The Philippines through the lens of an American soldier (1989-1907) the Harry Whitfield Harnish photographic collection (Manila Philippine Commission on Culture and Arts ; Art Studies Foundation; University Library UPD; Studio-Lab on Architecture History, UP College of Architecture, 2004)
This collection of photographs and perspectives on aspects of Philippine social life dwells on the vision of an American soldier as well as on the interdisciplinary outlook of critics of representation and its ramifications. Harry Witfield Harnish was stationed in the Philippines during the American imperialist occupation of the islands. Returning the look of the dominant gaze of exploration and surveillance unsettles the imagination of conquest as it redeems the possibility of a reciprocal and resistive exchange of sights in the present.--container.
CDROM
Gerard Rey Lico, project director / editor-in chief.
Keywords: Harnish, Harry Whitfield, 1898-1960 -- Photograph collections; Philippines -- History -- 1898 -- Pictorial works